The role of gender in health insurance enrollment among geriatric caregivers: results from the 2022 informal caregiving, health, and healthcare survey in Ghana - Williams Agyemang-Duah; Michael Safo Oduro; Prince Peprah; Dina Adei; Jacob Oppong Nkansah (BMC, 2024)
Abstract Background Female informal caregivers of older adults experience a higher burden of physical and mental health problems compared to their male counterparts due to the greater intensity of care they provide. This is likely to result in an imbalance in health needs, including health insurance enrollment, between male and female informal caregivers of older adults. However, to date, no study is available on the role of gender in health insurance enrollment among informal caregivers of older adults in Ghana. This study examines the association between gender and health insurance enrollment among informal caregivers of older adults in Ghana. Methods Cross-sectional data from the Informal Caregiving, Health, and Healthcare Survey among caregivers of older adults aged 50 years or above (N = 1,853 and mean ages =   39.15 years and  75.08 years of informal caregivers and their care recipients, respectively) in Ghana were analyzed. A binary logit regression model was used to estimate the association between gender and health insurance enrollment. All statistical inferences were made at the 5% significance level. Results The final Model (3) showed that female informal caregivers were 2.70 times significantly more likely to enrol in a health insurance scheme than their male counterparts (AOR: 2.70, 95% CI: 2.09-3.48, p-value = 0.001). Apart from gender, the results revealed that participants aged 55-64 years (AOR = 2.38, 95%CI: 1.29-4.41, p-value = 0.006), with tertiary education (AOR: 3.62, 95% CI: 2.32-5.66, p-value = 0.001) and living with the care recipients (AOR: 1.50, 95% CI: 1.14-1.98, p-value = 0.003) were significantly more likely to enrol in a health insurance scheme than their counterparts. The findings further showed that those who earned between GH¢1000 and 1999 (US$99.50-198.50) monthly (AOR: 0.70, 95% CI: 0.52-0.95, p-value = 0.022) and were affiliated with African traditional religion (AOR: 0.30, 95%CI: 0.09-0.99, p-value = 0.048) were significantly less likely to enrol in a health insurance scheme than their counterparts. Conclusion Gender was a significant predictor of health insurance enrollment among informal caregivers of older adults. This finding contributes to the empirical debates on the role of gender in health insurance enrollment among informal caregivers of older adults. Policymakers need to develop gender-specific measures to address gender gaps in health insurance enrollment among informal caregivers of older adults in Ghana. Such health policies and programs should consider other significant demographic and socioeconomic factors associated with health insurance enrolment among informal caregivers of older adults in Ghana.